Educomunicação : as imagens racializadas de crianças indígenas na mídia telejornalística - Mendonça, Wesley Souza (2020)
Modern rationality conformed communication as a disciplinary instrument for social bodies and ended education as a normative mechanism for the desired social order. Due to this orchestration, the image of the indigenous child has been crystallized in the social symbolic imagery through television news media speeches, to a large extent, universalizing. Inspired by an apparent “benevolence”, discursive productions tend to disseminate, at times, a certain archetype due to the absolutist and controversial view, taking the indigenous child as an exotic and representative of a people from the past, but also as a potential student and guardian of culture. Media rhetoric builds a cultural pedagogy that directly affects the social vision of indigenous children. Considering the deterministic, vertical and hierarchical logic that can perpetuate cultural domination and its consequences due to the asymmetry between indigenous and non-indigenous people, the objective of this investigation was to analyze the treatment given by the telejournalistic media to indigenous children, particularly by Rede Globo de Televisão, when rise in the news agenda and how the speeches given by it can produce the image of indigenous childhoods in social consciousness. Based on the theoretical contributions of media studies, notably, the assumptions of John B. Thompson, in educommunication as a proposal for a critical media pedagogy and in Child Sociology and Anthropology, the present research has as its corpus of analysis telejournalistic constructions on children indigenous, produced by broadcasters that make up the Globo Television Network, broadcast on an open channel and made available on the G1 news portal, between December 2012 and March 2018. The methodology used is the Depth Hermeneutics, proposed by John B. Thompson, structured in three phases: socio-historical analysis, formal or discursive analysis and interpretation / reinterpretation. The analysis of the television news collected shows that indigenous children occupy a restricted space in the media, and that, when they appear, they are associated with contexts of vulnerability, violence and / or in stigmatizing situations, therefore, due to the analyzed media discourse, they are represented in faces. racialized. In the set of pieces examined, the news media still reverberates with a deteriorated image of an indigenous child. Such an archetype can maintain an illusory view of reality, therefore, not corresponding to the existence of indigenous childhoods and, thus, corroborate for public policies that racialize and maintain relations of power, domination and oppression. Therefore, it is urgent to reflect on the symbolic constructions directed at indigenous children, produced and supported by the media, since they can circumscribe them in representation regimes and these, in turn, tend to engender systems of governability of their bodies and ways of existing.